1986
DOI: 10.1139/m86-053
|View full text |Cite
|
Sign up to set email alerts
|

Manganese and antibiotic biosynthesis. III. The site of manganese control of patulin production in Penicillium urticae

Abstract: Although manganese had been shown to be an essential requirement for patulin biosynthesis, its site of action was unknown. Four possibilities were considered. A manganese requirement for the second pathway enzyme, a decarboxylase, was discounted since mid and late pathway intermediates were not converted to patulin in manganese-deficient cultures. A major disruption in primary metabolism and hence secondary metabolism was discounted since eight primary metabolism enzymes showed no evidence of unusual changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The results in Fig. 1 (43,53), this is, to our knowledge, the first instance in which Mn regulation of gene transcription has been examined on a molecular level, and further study will be required to clarify the mechanisms involved.…”
Section: Discussionmentioning
confidence: 80%
“…The results in Fig. 1 (43,53), this is, to our knowledge, the first instance in which Mn regulation of gene transcription has been examined on a molecular level, and further study will be required to clarify the mechanisms involved.…”
Section: Discussionmentioning
confidence: 80%
“…Inhibitor studies using actinomycin D and cycloheximide showed that manganese exercised its affect on patulin biosynthesis at the level of transcription and influenced the coordinated appearance of pathway enzymes [54]. This was confirmed by Northern Blot analysis [29].…”
Section: Biosynthesis Of Patulinmentioning
confidence: 92%
“…This is consistent with the necessity of using an Mn+Z-free production medium in the production of citric acid where an addition of a very small amount of Mn +2 is sufficient to significantly decrease the final yield of citric acid by A. niger (Clark et al 1966;Shu and Johnson 1948). In a culture of P. urtieae, Mn +2 at an initial medium concentration of 1.5 ~tM was sufficient to maintain a high level of I C D H activity (Scott et al 1986b). In F. culmorum, the mitochondrial I C D H activity is low during 3-ADN production, indicating an overall low TCA cycle activity (Miller and Blackwell 1986).…”
Section: Effect Of Manganese On the Tca Cyclementioning
confidence: 99%